Review of The Production of Biodiesel from Waste Cooking Oil Using Acid/Alkaline Based Catalysts - Nizam, Nurul Athirah; Misdan, Nurasyikin (Progress in Engineering Application and Technology, 2022)
Biodiesel has proved to be the greatest substitute for diesel due to its unique characteristics, such as substantial reductions in greenhouse gas emissions, non-sulfur emissions, non-particulate matter pollutants, low toxicity, and biodegradability. In its most basic definition, it is a mono alkyl ester of long-chain fatty acids having characteristics that are similar to those of fossil-fuel-derived diesel. Waste cooking oil (WCO), which has tremendous potential as a raw material, may be used to make biodiesel. In the case of waste cooking oil with a high proportion of free fatty acids, an alkaline catalyst combines with the free fatty acids to generate soap through the saponification process. It also lowers biodiesel conversions. Waste cooking oil is processed with an acid catalyst to undergo an esterification reaction, which also requires high working conditions, in order to minimize the quantity of fatty acid concentration. This study investigated the benefits and drawbacks of different catalysts, such as homogeneous or heterogeneous catalysts, that have been used in recent years. Previous research has shown that the kind of catalyst may be selected based on several characteristics impacting the biofuel production process, such as reaction rate, catalyst concentration, temperature, catalyst type, alcohol used, alcohol to oil ratio, free fatty acid content, and water content.